Zanzibar's Foreign Relations with Western and European Countries 1856-1870 - Hammadi, Shaima Musa Jassim; Abd, Mosleh Muhammad (Journal of Tikrit University for Humanities, 2023)
The research dealt with Zanzibar's foreign relations with Western and European countries during the period of Sultan's rule 1856-1870. The study focuses on relations of Zanzibar with the United States of America. It dates back to the era of Sayyid Saeed bin Sultan, who signed the first treaty Business with the USA 1833 to regulate relations between the two countries. Sultan Majid, after the death of his father, continued to care for the development of these relations, a matter that increased exchanged trade and established agencies. The study, further, examines commercial relationships between Britain and Zanzibar and thus discusses trade treaties Signed by Sultan Majid with Britain in 1864 AD to ban slave trade. In addition, the study explained the commercial relations between Zanzibar and France and the role of Sultan Majid bin Said in developing these relationships. The study deals also with commercial relations between the German states and Zanzibar and the measures taken by Sultan Majid bin Said to develop relations and hold treaty of 1859, which incorporated trade relations between the two countries and facilitated the process of trade exchange and freedom of buying and selling and determining duties of customs.